Cervical Ripening With Prostaglandin Gel and Hygroscopic Dilators. Issue 1 (1998) - Hibbard, J. U.; Shashoua, A.; Adamczyk, C.; Ismail, M.
Abstract : Objective: To study the effectiveness and morbidity of adding hygroscopic cervical dilators to prostaglandin gel for cervical ripening and labor induction. Study design: Patients of at least 34 weeks' gestation with a medical indication for induction of labor and with a modified Bishop score of 5 or less were randomized to receive either prostaglandin gel or prostaglandin gel with hygroscopic cervical dilators. Primary outcomes were time to delivery, change in cervical score, and infection. Secondary outcomes included cesarean delivery rate and deliveries before 24 hours of induction. Continuous variables were analyzed by Wilcoxon sum rank test and categorical data by chi-square or Fisher exact test, with P < 0.05 being significant. Results: Seventeen patients were randomized to intracervical prostaglandin alone and 23 patients received intracervical prostaglandin plus hygroscopic dilators. No demographic differences were noted between the groups. After six hours of ripening, the combined group achieved a greater change in Bishop score (3.6 vs. 2.1, P = 0.007) and tended to have a shorter induction time (21.7 vs. 26.4 hours, P = 0.085). The combined therapy group had a higher infection rate than the prostaglandin-only group (59% vs. 12%, P = 0.003). Conclusion: Combining cervical dilators with prostaglandin gel provides more effective cervical ripening and a more rapid induction to delivery interval than prostaglandin alone but with a significant and prohibitive rate of infection.